Maternal melatonin treatment rescues endocrine, inflammatory, and transcriptional deregulation in the adult rat female offspring from gestational chronodisruption - Mendez, Natalia; Halabi, Diego; Salazar-Petres, Esteban Roberto; Vergara, Karina; Corvalan, Fernando; Richter, Hans G.; Bastidas, Carla; Bascur, Pía; Ehrenfeld, Pamela; Seron-Ferre, Maria; Torres-Farfan, Claudia (Frontiers in Neuroscience, 2022)
Gestational chronodisruption impact maternal circadian rhythms, inhibiting the nocturnal increase of melatonin, a critical hormone that contributes to maternal changes adaptation, entrains circadian rhythms, and prepares the fetus for birth and successful health in adulthood. In rats, we know that gestational chronodisruption by maternal chronic photoperiod shifting (CPS) impaired maternal melatonin levels and resulted in long-term metabolic and cardiovascular effects in adult male offspring. Here, we investigated the consequences of CPS on mother and adult female offspring and explored the effects of melatonin maternal supplementation. Also, we tested whether maternal melatonin administration during gestational chronodisruption rescues maternal circadian rhythms, pregnancy outcomes, and transcriptional functions in adult female offspring. Methods: Female rats raised and maintained in photoperiod 12:12 light: dark were mated and separated into three groups: a) control photoperiod 12:12 (LD); b) CPS photoperiod; and c) CPS+Mel mothers supplemented with melatonin in the drinking water throughout gestation. In the mother, we evaluated maternal circadian rhythms by telemetry and pregnancy outcomes, in the long-term, we study adult female offspring by evaluating endocrine and inflammatory markers and the mRNA expression of functional genes involved in adrenal, cardiac, and renal function. Results: In the mothers, CPS disrupted circadian rhythms of locomotor activity, body temperature, and heart rate and increased gestational length by almost 12-h and birth weight by 12%, all of which were rescued by maternal melatonin administration. In the female offspring, we found blunted day/night differences in circulating levels of melatonin and corticosterone, abnormal patterns of pro-inflammatory cytokines Interleukin-1a (IL1a), Interleukin-6 (IL6), and Interleukin-10 (IL10); and differential expression in 18 out of 24 adrenal, cardiac, and renal mRNAs evaluated. Conclusion: Maternal melatonin contributed to maintaining the maternal circadian rhythms in mothers exposed to CPS, and the re-establishing the expression of 60% of the altered mRNAs to control levels in the female offspring. Although we did not analyze the effects on kidney, adrenal, and heart physiology, our results reinforce the idea that altered maternal circadian rhythms, resulting from exposure to light at night, should be a mechanism involved in the programming of Non-Communicable Diseases.